PENGEMBANGAN PENUNTUN PRAKTIKUM KOLOID BERBASIS INKUIRI TERBIMBING PADA SISWA DI KELAS XI IPA SMA NEGERI 1 SUNGAI RAYA - Tika Pratiwi; Dedeh Kurniasih; Rizmahardian Azhari Kurniawan (Universitas Muhammadiyah Pontianak, 2018)
Colloid is chemistry material which can be teached by experiment method. However, teacher’s practical guide didn’t match with the students characteristics and laboratory equipment in SMA Negeri 1 Sungai Raya. Therefore, this research aimed to develope the colloid practical guide based on guide inquiry. This research method was used Borg and Gall’s development model. Sampling technique used in this research was purposive sampling technique. Samples are students at eleventh grade in IPA 1 and IPA 2 SMA Negeri 1 Sungai Raya. The data was collected by using questionnaires and posttest sheet. The results of the research showed that the colloid practical guide are valid, practice, and effective. Validity test consists of three aspects (content, media, and language) were obtained coefficient validity with the average 1.00 or can be categorized